1984
DOI: 10.1111/j.1365-2133.1984.tb06601.x
|View full text |Cite
|
Sign up to set email alerts
|

IgA anti-endomysium antibody. A new immunological marker of dermatitis herpetiformis and coeliac disease

Abstract: The recently described IgA anti-endomysial antibodies (IgA-EmA) are directed against the intermyofibril substance of the smooth muscle, which may correspond either to a reticulin-like structure or a surface component of smooth muscle fibrils. These antibodies occurred in about 80% of sera of thirty-eight patients with dermatitis herpetiformis (DH), in about 70% of twenty-eight patients with coeliac disease and in about 20% of nine patients with other enteropathies. IgG class anti-gliadin antibodies (AGA) also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
143
2
9

Year Published

1986
1986
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(156 citation statements)
references
References 15 publications
2
143
2
9
Order By: Relevance
“…EMA was determined by indirect immunofluorescence on monkey esophagus (BINDAZYME™, The Binding Site Ltd, Birmingham, UK) as previously described. 22 Positive = ≥1:5. HLA class II was typed by low-resolution PCR-SSP (one Lambda Inc., Canoga Park, CA), and by high resolution methods for DQA/B alleles.…”
Section: Patientsmentioning
confidence: 99%
“…EMA was determined by indirect immunofluorescence on monkey esophagus (BINDAZYME™, The Binding Site Ltd, Birmingham, UK) as previously described. 22 Positive = ≥1:5. HLA class II was typed by low-resolution PCR-SSP (one Lambda Inc., Canoga Park, CA), and by high resolution methods for DQA/B alleles.…”
Section: Patientsmentioning
confidence: 99%
“…All EMA had been analyzed at the Clinical Microbiology and Immunology, Lund University Hospital, Lund, Sweden, by indirect immunofluorescence [5]. …”
Section: Endomysial Autoantibody Immunofluorescence (Ema)mentioning
confidence: 99%
“…For the laboratory diagnosis of celiac disease (CD) determination of endomysial antibodies (EMA) has long been utilized [5]. It has further been shown that tTG is the main autoantigen of EMA [6].…”
Section: Introductionmentioning
confidence: 99%
“…Las únicas situaciones en las que podría mantenerse la utilización de estos marcadores son el control de la dieta sin gluten y la falta de sensibilidad de los anticuerpos antiendomisio (AEm)-IgA por debajo de los 2 años de edad, aunque en estos casos, los AAG se ven superados por sus sucesores naturales, los anticuerpos antipéptidos deaminados de gliadina 53 . La descripción del patrón de AEm-IgA en la dermatitis herpetiforme y la EC por inmunofluorescencia indirecta sobre cortes de esófago de mono 54 o de cordón umbilical humano 55 revolucionó el diagnóstico serológico de la EC, y se alcanzaron unas cifras de sensibilidad y especificidad superiores al 95% 51 . Además de la utilización de los tejidos de mono, el principal problema de estos marcadores es técnico, puesto que la inmunofluorescencia indirecta requiere la interpretación del observador, es, por tanto, subjetiva, y necesita de un entrenamiento especial y experiencia.…”
Section: Marcadores Serológicosunclassified